Assessing water-related plant traits to explain slow-wilting in soybean PI 471938. Issue 3 (4th May 2017) - Bagherzadi, Laleh; Sinclair, Thomas R.; Zwieniecki, Maciej; Secchi, Francesca; Hoffmann, William; Carter, Thomas E.; Rufty, Thomas W.
ABSTRACT: Soybean [ Glycine max (L.) Merr.] genotype PI 471938 expresses a slow-wilting phenotype in the field, and the progeny of this genotype have shown to have high yield under water deficit conditions. However, the physiological basis for the slow-wilting trait in PI 471938 remains unclear, and failure to understand the causal mechanism may limit future breeding efforts. This study investigated three primary hypotheses for trait expression that could explain slow-wilting trait in PI 471938: (1) a low osmotic potential in the leaves allowing greater water retention, (2) high elastic modulus of leaves resulting in delayed development of wilting, and (3) high hydraulic conductance allowing rapid water redistribution in the plants. Experiments included three other soybean genotypes as references for the results obtained with PI 471938. Surprisingly, the results for PI 471938 did not prove to be unique as compared to the other three tested genotypes for any of the three hypotheses. These negative results indicate that a hypothesis outside the usual candidates describing plant water transport, possibly anatomical features related to specific water transport properties, is required to explain slow-wilting in PI 471938.